Gold nanoparticles-mediated photothermal therapy and immunotherapy. (21st September 2018) - Liu, Yang; Crawford, Bridget M; Vo-Dinh, Tuan
Cancer has been a significant threat to human health with more than eight million deaths each year in the world. Therefore, there is a significant need for novel technologies to effectively treat cancer and ultimately reduce cancer recurrences, treatment costs, number of radical cystectomies and mortality. A promising therapeutic platform for cancer is offered by nanoparticle-mediated therapy. This review highlights the development and applications of various nanoparticle platforms for photo-induced hyperthermia and immunotherapy. Taking advantage of gold's high biocompatibility, gold nanoparticles (GNPs) can be injected intravenously and accumulate preferentially in cancer cells due to the enhanced permeability and retention effect. Various gold nanoplatforms including nanospheres, nanoshells, nanorods, nanocages and nanostars have been used for effective photothermal treatment of various cancers. GNPs have also been used in immunotherapies, involving cancer antigen and immune adjuvant delivery as well as combination therapies with photothermal therapy. Among GNPs platforms, gold nanostars (GNS) have great therapeutic potential due to their unique star-shaped geometry that dramatically enhances light absorption and provides high photon-to-heat conversion efficiency due to the plasmonic effect. This photothermal process can be exploited to specifically ablate tumors and, more importantly, to amplify the antitumor immune response following the highly immunogenic thermal death of cancer cells. GNS-mediated photothermal therapy combined with checkpoint immunotherapy has been found to reverse tumor-mediated immunosuppression, thereby leading to the treatment of not only primary tumors but also cancer metastasis, as well as to induce effective long-lasting immunity, in other words, an anticancer 'vaccine' effect.